2020
DOI: 10.1016/j.cub.2019.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Transient Membrane-Linked FtsZ Assemblies Precede Z-Ring Formation in Escherichia coli

Abstract: Highlights d Z-ring formation in E. coli is preceded by formation of transient FtsZ assemblies d The assemblies show rapid growth and shrinkage in addition to treadmilling d Transient assemblies compete for the available FtsZ pool d FtsZ protofilaments in the cytosol are less than 20 monomers long

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 50 publications
7
30
0
Order By: Relevance
“…During the nascent Z-ring stage, low density FtsZ filaments transiently assemble at mid-cell over a wide 92 region, consistent with previous reports 4, [13][14][15] . FtsZ filaments then rapidly condense into a thin mature Z-ring structure, which remains unconstricted but increases in intensity for some time.…”
supporting
confidence: 91%
“…During the nascent Z-ring stage, low density FtsZ filaments transiently assemble at mid-cell over a wide 92 region, consistent with previous reports 4, [13][14][15] . FtsZ filaments then rapidly condense into a thin mature Z-ring structure, which remains unconstricted but increases in intensity for some time.…”
supporting
confidence: 91%
“…Our results confirm this for PaFtsZ. Recently, two studies that measured the effect of ZapA on treadmilling of FtsZ, and found that ZapA did not slow the FtsZ treadmilling rate in vitro 49 and in vivo 50 . Overall these results suggest that the bundling of FtsZ pfs by ZapA is loose enough that it does not significantly alter treadmilling.…”
Section: Discussionsupporting
confidence: 90%
“…The structure shows that the GDP is trapped in a pocket with no channel that could permit its escape. Now that treadmilling is established as the mechanism for assembly dynamics [14][15][16]49,50 , we can assume that the rate of GTP hydrolysis at steady state measures the rate at which subunits associate to the bottom and dissociate from the top of pfs.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of FtsZ polymerization is obviously crucial to counteract FtsZ ring formation prior to the start of cell division, but it is still required at other times to prevent aberrant ring formation by the majority of cellular FtsZ that is present outside the central ring (20). Furthermore, as nonring FtsZ seems to form oligomers transiently attached to the membrane (20,21), inhibition at this location becomes crucial and the cell has developed a robust mechanism based on the action of the Min system. Our results support the idea that SlmA likely acts coordinately with this system at the membrane.…”
Section: Discussionmentioning
confidence: 99%